Peningkatan Status Kesehatan Masyarakat melalui Penyuluhan Dampak Negatif Merokok dan Kaitannya dengan Hipertensi pada penduduk di Desa Amiria Bahagia Kecamatan Simeulue Timur, Kabupaten Simeulu - Sofia, Sofia -; Juwita, Juwita; Miftahuddin, Miftahuddin; Maulana, Teuku; Hafifatunnur, Hafifatunnur; Azhary, Dany; Jannah, Syarifah Raihannatul (Universitas Syiah Kuala, 2024)
Cigarette smoke is one of the causes of air pollution which can have adverse health effects. The number of smokers in Indonesia has increased in the last 10 years, thus the high prevalence of smoking harms people's health. One of the significant impacts on thehuman body is on thecardiovascular system, i.e, increasing blood pressure. Data from the East Simeulue Health Service 2023 recorded that the number of people experiencing hypertension reached 1,344 people. The high prevalence of hypertension in the East Simeulue sub-district is in line with the high prevalence of people who smoke in this area. Therefore, this community service activity aims to increase the understanding and knowledge of the inhabitants of Amiria Bahagia Village, East Simeulue District regarding the impact of smoking on health and incidences of hypertension. This activity was divided into two sessions: a health socialization and a blood pressure examination. The result from the health examinations found that for hypertension 31 (34,10%) respondents and non-hypertension 60 (65,90%) respondents out of the total 91 respondents. Of the smoking status, there are 52 (57,10%) respondents were smokers and 39 (42,90%) respondents were non-smokers. It is hoped that the results of this activity will increase public knowledge regarding the negative effects of smoking and risk factors for hypertension in the population of East Simeulue sub-district. The knowledge conveyed can contribute to improve the quality of public health and reduce the incidences of hypertension in the community.